Modeling and analyzing of high-speed maglev train-bridge systems considering centrifugal force induced by bridge vertical deformation - Tian, Xiangfu; Xiang, Huoyue; Li, Yongle (Structures (Oxford), 2025)
This study aims to investigate the dynamic response of a high-speed maglev train-bridge system by considering the centrifugal force induced by vertical bridge deformation. A framework for dynamic response analysis is developed, where the motion equations of the maglev train moving on a vertical deformation are established using the trajectory coordinate system. The central difference method is used to calculate the curvature of vertical deformation of bridges. The train and bridge systems are coupled through an electromagnetic force model, applying appropriate coordinate transformations. The framework is employed to analyze the coupled vibration mechanism of the maglev train-bridge system, considering centrifugal force, based on a guideway and a continuous rigid frame bridge. Moreover, the effects of bridge deformation curvature, train speed and pre-camber are discussed. The results reveal that the centrifugal force caused by vertical bridge deformation significantly influences the system's dynamic response at high speeds. Specifically, for guideways, the centrifugal force can be neglected when the train speed is below 500 km/h, but must be considered above this threshold. For continuous rigid frame bridges, the centrifugal force must be accounted for when the train speed exceeds 300 km/h. Additionally, it is found that the vehicle's response to centrifugal force can be mitigated by adjusting the bridge pre-camber. This study introduces a novel approach by incorporating centrifugal force effects due to bridge vertical deformation into the dynamic analysis of the maglev train-bridge system, offering valuable insights into the influence of high-speed train operation on infrastructure design.